EFFECT OF CALCINATION TEMPERATURE ON THE ADSORPTION PERFORMANCE OF MG/AL LAYERED DOUBLE HYDROXIDE NANOPARTICLES IN THE REMOVAL OF MEROPENEM ANTIBIOTICS - Yaseen Rashid Hasan,; Mohammed Ali A. Shaban,; Mohammed A. Ibrahim,; Mohanad J. M-Ridha,; Haitham A. Hussein, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
Meropenem (MER) antibiotic is removed from an aqueous solution using Mg-Al-layered double hydroxide (Mg/Al-LDHs) which serves to functionalize the principal object of enquiry in this paper–sunflower husks (SFH).  The former sample demonstrated a 51% removal of MER while the latter demonstrated a 67% removal of MER. One of the areas explored was the impact of the rise calcination temperatures resulted in a concurrent increase in the surface area and porosity of LDHs which, in turn, provoked a heightened removal efficacy of MER at calcination temperatures between 300 °C and 350 °C. Nonetheless, LDHs experienced structural deformation and thus, diminished removal efficacy of MER when the calcination temperature was over 350 °C. The ideal adsorption conditions were determined via the undertaking of multiple batch studies. Adsorption process was implemented successfully with removal efficiency of 98% under optimal conditions. The adsorption of MER was found to be regulated by the chemisorption mechanism of the best suited second order kinetic model. The adsorption process seemed to be heterogeneous and on a multi-layer as suggested by the high determination coefficient with Freundlich model. Enhanced functional and structural properties were witnessed in this novel adsorbent’s adsorption capacity, thereby highlighting its proficiency as an alternative.